2020
DOI: 10.1186/s12866-020-01778-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of surface proteins in a clinical Staphylococcus haemolyticus isolate by bacterial surface shaving

Abstract: Background: The skin commensal Staphylococcus haemolyticus is an emerging nosocomial pathogen. Despite its clinical relevance, published information about S. haemolyticus virulence factors is scarce. In this study, the adhesive and biofilm forming properties of ten clinical and ten commensal S. haemolyticus strains were examined using standard adhesion and biofilm assays. One of the clinical strains was used to identify expressed surface proteins using bacterial surface shaving. Protein abundance was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…Surface shaving analysis identified 65 surface proteins, including 3 adhesins, extracellular matrix binding protein (Embp), Mannosylglucosyl-3-phosphoglycerate phosphatase (SasH-like) and others. Upon colonization, an increase in SceD and the autolysin Atl genes was observed [ 43 ]. In fact, no previous reports have clearly detected FnBP proteins inCoNS [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surface shaving analysis identified 65 surface proteins, including 3 adhesins, extracellular matrix binding protein (Embp), Mannosylglucosyl-3-phosphoglycerate phosphatase (SasH-like) and others. Upon colonization, an increase in SceD and the autolysin Atl genes was observed [ 43 ]. In fact, no previous reports have clearly detected FnBP proteins inCoNS [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adherence property of clinical S. haemolyticus is different from commensal S. haemolyticus. Commensal S. haemolyticus have high adherence to fibronectin and collagen, while clinical S. haemolyticus have low adherence to fibronectin and collagen [123]. However, using the bacteria surface shaving approach, 65 surface proteins were identified in clinical S. haemolyticus isolates and were associated with adherence to human keratinocytes such as the bacterial Toll/interleukin-1 like (TIRs) domain-containing protein, the bifunctional autolysin Atl, LPXTG, and the transglycosylase SceD [123].…”
Section: S Haemolyticus Surface Proteins Required For Bacteria Adherencementioning
confidence: 99%
“…The importance of using culture media mimicking the conditions of infection was highlighted by Liu et al, who found a total of 121 outer membrane proteins produced by B. cenocepacia strain Y10 after cultivation in different media, 37 proteins being uniquely identified when the cells were cultivated in ASM [48]. Wolden and colleagues also performed the cell-shaving technique with Staphylococcus haemolyticus after the bacterium's cultivation in the presence of keratinocytes, highlighting the importance of the use of the technique after host-microbe interaction [49].…”
Section: Discussionmentioning
confidence: 99%